An Exploratory Study of Gender Differences in Clinical Profile and Pathways to Care in Somatic Symptom Disorder - Sheena K. Agarwal; Anil Kumar M. Nagaraj (Indian Journal of Social Psychiatry)
Background: Research shows that men and women with somatic symptom disorder (SSD) present differently, with higher rates of symptom reporting, and comorbidity in women. However, most studies have looked into the gender differences in the areas of prevalence and stability of somatic symptoms over time. Thus, the literature on the gender differences in the detailed clinical profiles of men and women with SSD and their pathways to care is scant. Aim: We aimed to study the gender gap in the clinical profile and pathways to care in SSD. Methods: This is a cross-sectional, exploratory, hospital-based study from a tertiary care hospital in South India. One hundred-seven patients (51 males, 56 females) aged 18–60 years were comprehensively assessed using MINI International Neuropsychiatric Interview 7.0.2, Clinical Global Impression-Severity (CGI-S), Depression, Anxiety, and Stress Scale 21 items (DASS 21), WHO Somatoform Disorders Schedule (SDS), and the pathway to care encounter form. Results: Stress as assessed by DASS 21 was significantly high among females. Comorbidities were evenly matched. On the WHO SDS, women reported pain and genitourinary symptoms significantly higher than men. There was a statistically significant difference in whom men and women chose as the first carer, but not the subsequent carers. Conclusion: This unique study explored SSD in detail. We found isolated areas where men and women differ in clinical profile and pathway to care. Overall, the difference in morbidity status appears minimal, although existing evidence shows that women present with higher morbidity.